Hyperbranched polydendrons: a new nanomaterials platform with tuneable permeation through model gut epithelium. Issue 1 (14th October 2014) - Hatton, Fiona L.; Tatham, Lee M.; Tidbury, Louise R.; Chambon, Pierre; He, Tao; Owen, Andrew; Rannard, Steven P.
Abstract : Highly branched vinyl polymers (hyperbranched polydendrons), displaying combinations of dendritic and PEG end groups, have been synthesised using a mixed initiator approach. Nanoprecipitated polydendron particles have exhibited controlled permeation through a gut epithelium model. Abstract : The development of nanomaterials for advanced therapies requires the formation of versatile platforms that may be tuned to maximize beneficial attributes and minimize unwanted negative behaviour. Additionally, the optimum route of administration is a key consideration of any new treatment and much work has been focused on direct injection into the systemic circulation rather than oral delivery. Here we describe a new approach to polymeric nanoparticle design and present initial results showing the potential for tuneable permeation through a gut epithelium model. Through the use of mixed initiators and branched vinyl polymerization, a series of systematically varying branched polymers have been synthesized and nanoprecipitated. The surprisingly uniform structures have undergone preliminary pharmacological evaluation to establish low cytotoxicity and enhanced permeation through model intestinal epithelial cells. This presents potential opportunities for future developments that may allow oral dosing to result in circulating polymeric nanoparticles; behaviour that may prove clinically desirable to many non-terminal or chronic diseases that utilise nanomedicines but wish to avoid regular or repeated intravenous administration.